Cativeiros do agronegócio no campo brasileiro: uma análise da escravidão contemporânea a partir do Oeste da Bahia - Santana, Aurelane Alves (2022)
This thesis aims to discuss the connection between slave labor and the development of capitalism. For this purpose, it focuses on the analysis of the functionality and historical contribution of colonial slavery in the process of primitive accumulation of capital and the socioeconomic factors that cause the reproduction of labor relations analogous to slavery in the 21st century. The idea is to move away from an understanding of contemporary slave labor as an anomaly inside the capitalist system - in other words, as a phenomenon that results from the coexistence of the archaic and the modern, in which labor relations do not keep up with the advance of constant capital and remain backward and seen as elements inherent only to the beginnings of capitalism. With this purpose, the study is based on the characteristics of the nature of capital to show that the exploitation of the worker to the maximum, that is, to exhaustion, is intrinsic to capitalist expansion, not being, therefore, something strange to the sociability that this mode of production imposes in time and space. Linked to this perspective, it is evident that, besides being a product of the nature of capital, contemporary slave labor also results from the convergence of several economic, political, legal, and socio-spatial factors that make its reproduction possible through the correlation of forces between social classes, historically unfavorable to workers, and the actions of the State. The discussion begins by showing how slavery was used in the American continent and in Brazil as a primary source of labor to generate wealth for the European metropolises, to promote the development of capitalism based on the primitive accumulation of capital and to consolidate the class structures in the colonies. With the abolition of slavery and the implementation of the Brazilian labor market, the forms of exploitation that started to be performed by the capital resulted in the excessive consumption of labor power, with numerous attempts to extend the working day, the incorporation of different mechanisms to retain added value, the low remuneration, etc. In the face of these given labor conditions, we discuss how the processes of struggles of the working class were and are fundamental in the conquest of labor rights, since neither capitalists nor the modern State set limits regarding the exploitation of labor. As an example of this reality, we analyze the incidence of labor analogous to slavery in rural areas of Bahia – especially in the western region of this state – and its relation to the expansion of agribusiness that concentrates land and appropriates forms of exploitation and expropriation that make the workers' living conditions more precarious and degraded. The conclusion reached is that there is no incompatibility between the existence of labor analogous to slavery and the modern production of commodities verified in agribusiness in the west of Bahia. This is justified by the fact that the contemporary reproduction of labor relations similar to slavery results from the unequal and combined development of capital that propitiates the division of labor from the conjunction of distinct economic, political, legal, and socio-spatial conditions of a determined social formation, as well as the specific nature of capital to reproduce forms of labor exploitation that increase the extraction of overwork and that converge to the reproduction of labor analogous to slavery nowadays.